2017
DOI: 10.1080/14786419.2017.1309533
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic acid changes the composition of essential oil isolated from narrow-leaved lavender propagated in in vitro cultures

Abstract: The aim of the present study was to determine the effect of jasmonic acid added to the culture medium on composition of Lavandula angustifolia essential oils. The chemical composition was determined by gas chromatography coupled to mass detector (GC/MS). The experiment was conducted with the use of MS medium supplemented with increasing concentration of JA (0.2, 0.5, 1, 1.5 mg∙dm). It was found that the analysed essential oils varied in terms of chemical composition depending on the content of JA in the medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…At the concentration of 50%, all the essential oils isolated from the plants grown on the media with the addition of JA, regardless of its concentration, exhibited stronger activity towards C. albicans (9.7-12.3 mm) in comparison with the control. In our previous research (Andrys et al 2017), we had observed that the essential oils isolated from plants grown in vitro on media with the addition of JA had a different chemical composition from plants propagated on media without an elicitor. The addition of jasmonic acid to the medium resulted in an increase in the amount of compounds such as borneol -its concentration, obtained by using a medium with JA, amounted to 12.4-17.5%, with 6.7% in the control (medium without JA).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…At the concentration of 50%, all the essential oils isolated from the plants grown on the media with the addition of JA, regardless of its concentration, exhibited stronger activity towards C. albicans (9.7-12.3 mm) in comparison with the control. In our previous research (Andrys et al 2017), we had observed that the essential oils isolated from plants grown in vitro on media with the addition of JA had a different chemical composition from plants propagated on media without an elicitor. The addition of jasmonic acid to the medium resulted in an increase in the amount of compounds such as borneol -its concentration, obtained by using a medium with JA, amounted to 12.4-17.5%, with 6.7% in the control (medium without JA).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…4). Previous research had demonstrated that the addition of JA to the medium affected the chemical composition of essential oils and was responsible for the emergence of new compounds such as p-cymene (0.35-0.56%), cis β-terpineol (0.21-0.26%), linalool (0.36-0.60%), compared to the control (Andrys et al 2017). Those compounds may be partly responsible for the higher antioxidant activity of the extract isolated from plants grown on media with the addition of JA compared to the extract isolated from plants grown on the control medium.…”
Section: Polyphenol Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8-cineole (65.4%) and borneol (11.5%) dominated in the essential oils isolated from the leaves of L. angustifolia collected near Isfahan, Iran [32]. Borneol was the main compound in the essential oils isolated from leafy stems of three lavender cultivars propagated in in vitro cultures: ‘Blue River’ (25.75%), ‘Elegance Purple’ (32.17%), and Munstead (13.38%) [33].…”
Section: Resultsmentioning
confidence: 99%
“…Растения умеренного климата обычно хранят при температуре +2…+5 °С [3]. Жасмоновая кислота и метилжасмоновая кислота имеют важную регуляторную функцию при клональном микроразмножении винограда, лаванды, лилий и других культур, оказывая регулирующее влияние на синтез абсцизовой кислоты в микрорастениях [4][5][6]. Метилжасмонат увеличивает продолжительность хранения граната и лилий при низкой положительной температуре [5,7].…”
Section: Introductionunclassified